2023
DOI: 10.1021/acschembio.2c00945
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Isolated Escherichia coli DH5α Peptidoglycan Sacculi Identifies the Mechanism of Action of Cell Wall-Inhibiting Antibiotics

Abstract: Antibiotic resistance of pathogenic bacteria needs to be urgently addressed by the development of new antibacterial entities. Although the prokaryotic cell wall comprises a valuable target for this purpose, development of novel cell wall-active antibiotics is mostly missing today. This is mainly caused by hindrances in the assessment of isolated enzymes of the co-dependent murein synthesis machineries, e.g., the elongasome and divisome. We therefore present imaging methodologies to evaluate inhibitors of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Although we do not know why these observations using AFM obtained different results, our results are consistent with those of Elsbroek et al (2023) and are therefore consistent with our conclusion that the RMR-producing strain probably has reduced peptidoglycan synthesis activity. Furthermore, Salamaga et al (2021) reported that peptidoglycan purified from S. aureus cells treated with methicillin or vancomycin had larger holes than those purified from nontreated cells, using AFM.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although we do not know why these observations using AFM obtained different results, our results are consistent with those of Elsbroek et al (2023) and are therefore consistent with our conclusion that the RMR-producing strain probably has reduced peptidoglycan synthesis activity. Furthermore, Salamaga et al (2021) reported that peptidoglycan purified from S. aureus cells treated with methicillin or vancomycin had larger holes than those purified from nontreated cells, using AFM.…”
Section: Discussionsupporting
confidence: 86%
“…Turner et al (2018) reported that no change in the pore size of peptidoglycans was observed with the addition of A22. On the other hand, Elsbroek et al (2023) reported that the addition of β-lactam antibiotics made peptidoglycans less dense, that is, the pores became larger, in which the authors concluded that their results are consistent with the mechanism of action of β-lactam antibiotics to inhibit peptide cross-linking.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Typically, similar types of elongation have been described for bacteria with damaged cell wall formation (e.g. by fosfomycin or β-lactam antibiotics (Elsbroek et al 2023 ). This finding indicates that low acetylated chitosans interact with the correct cell wall formation, which again could explain also changes in the outer membrane.…”
Section: Resultsmentioning
confidence: 80%
“…This finding indicates that low acetylated chitosans interact with the correct cell wall formation, which again could explain also changes in the outer membrane. As cell wall architecture can be monitored more specifically by isolation and preparation of the murein sacculi of the bacteria and subsequent AFM imaging (Elsbroek et al 2023 ), those were isolated and purified from untreated C. jejuni (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%